Several Turán-Type Inequalities for the Generalized Mittag-Leffler Function - Xiang Kai Dou; Li Yin; Xiu-Li Lin (Journal of Function Spaces, 2020)
In this paper, several Turán-type inequalities for the more generalized Mittag-Leffler function are proved. In addition, we also gave affirmative answers to two open problems posed by Mehrez and Sitnik.